2016
DOI: 10.1111/psyp.12676
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of surface facial electromyography

Abstract: Data from two studies were used to estimate the reliability of facial EMG when used to index facial mimicry (Study 1) or affective reactions to pictorial stimuli (Study 2). Results for individual muscle sites varied between muscles and depending on data treatment. For difference scores, acceptable internal consistencies were found only for corrugator supercilii, and test-retest reliabilities were low. For contrast measures describing patterns of reactions to stimuli, such as high zygomaticus major combined wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 60 publications
(77 reference statements)
1
56
0
Order By: Relevance
“…Similarly, we focused on the activity of the corrugator muscle, because it is a reliable index of facial mimicry for happy, angry, and sad expressions [ 50 ], in contrast to the zygomaticus, the muscle pulling up the cheeks in smiling. Concerning the zygomaticus, Künecke et al [ 30 ], for example, found no significant differences in activity when participants viewed faces expressing different emotions.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, we focused on the activity of the corrugator muscle, because it is a reliable index of facial mimicry for happy, angry, and sad expressions [ 50 ], in contrast to the zygomaticus, the muscle pulling up the cheeks in smiling. Concerning the zygomaticus, Künecke et al [ 30 ], for example, found no significant differences in activity when participants viewed faces expressing different emotions.…”
Section: Introductionmentioning
confidence: 99%
“…In line with the Precision Medicine Initiative (Insel, Amara, & Baschke, 2015), identifying biological indicators that predict treatment response is critical. Prior to testing predictors, research must first examine core psychometric properties, including test-retest stability (i.e., invariance over time) and internal consistency (i.e., odd/even reliability; see Auerbach et al, 2016;Cassidy, Robertson, & O'Connell, 2012;Hess et al, 2017;Olvet & Hajcak, 2009;Tenke et al, 2017;Weinberg & Hajcak, 2011b). In research testing the EIT, Kujawa and colleagues (2013) showed 2-year stability of LPP amplitude in children 8 to 13 years old.…”
Section: Introductionmentioning
confidence: 99%
“…Facial EMG is used to quantify and identify emotions often characterizing positive and negative valence (as opposed to specific emotions). Consequently, many studies focus on the acquisition of Corrugator and Zygomaticus (negative vs.positive valence respectively; see (Larsen & Fredrickson, 1999), in part due to increased reliability of these signals when compared with emotion specific signals (Hess et al, 2017). The results indicated that…”
Section: Discussionmentioning
confidence: 99%
“…Facial EMG is used to quantify and identify emotions often characterizing positive and negative valence (as opposed to specific emotions). Consequently, many studies focus on the acquisition of Corrugator and Zygomaticus (negative vs.positive valence respectively; see (Larsen & Fredrickson, ), in part due to increased reliability of these signals when compared with emotion specific signals (Hess et al, ). The results indicated that Corrugator response discriminates negative facial stimuli (i.e., ‘Yuck’ face) from happy stimuli (i.e., ‘Smile’ face), an approach that could be leveraged for studying valence in addition to emotion‐specific responses.…”
Section: Discussionmentioning
confidence: 99%